K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 8 2020

\(F=-3\left(x-8\right)\left(2x+1\right)-\left(x+5\right)\left(2-3x\right)-4x\left(x-6\right)\)

\(=-3\left(-3-8\right)\left(-6+1\right)-\left(5-3\right)\left(2+9\right)+12\left(-9\right)\)

\(=-3\left(-11\right)\left(-5\right)-\left(-2\right)11-12.9\)

\(=-165+22-108=22-273=-251\)

\(G=\left(5x-4\right)\left(5-2x\right)-7x\left(x^2-4x+3\right)+\left(x^2-4x\right)\left(7x-2\right)\)

\(=\left(5-4\right)\left(5-2\right)-7\left(1-4+3\right)+\left(1-4\right)\left(7-2\right)\)

\(=3-7.0+5.\left(-3\right)=3-15=-12\)

\(H=\left(-3x+5\right)\left(x-6\right)-\left(x-1\right)\left(x^2-2x+3\right)+\left(x+2\right)\left(x^2-3\right)\)

\(=\left(3+5\right)\left(-1-6\right)-\left(-1-1\right)\left(1+2+3\right)+\left(-1+2\right)\left(1-3\right)\)

\(=8\left(-7\right)-\left(-2\right)6+1\left(-2\right)=-56+12-2=-46\)

1 tháng 8 2020

\(L=5x\left(x-1\right)\left(2x+3\right)-10x\left(x^2-4x+5\right)-\left(x-1\right)\left(x-4\right)\)

\(=-\frac{5}{3}\left(-\frac{4}{3}\right)\left(-\frac{2}{3}+3\right)+\frac{10}{3}\left(\frac{1}{9}+\frac{4}{3}+5\right)-\left(-\frac{4}{3}\right)\left(-\frac{1}{3}-4\right)\)

\(=\frac{20}{9}\left(\frac{7}{3}\right)+\frac{10}{3}\left(\frac{13}{9}+5\right)+\frac{4}{3}\left(-\frac{13}{3}\right)\)

\(=\frac{140}{27}+\frac{10}{3}.\frac{58}{9}-\frac{52}{9}\)

\(=\frac{140}{27}+\frac{580}{27}-\frac{156}{27}=\frac{140+580-156}{27}=\frac{720-156}{27}=\frac{564}{27}\)

\(M=-7x\left(x-5\right)-\left(x-1\right)\left(x^2-x-2\right)+x^2\left(x-3\right)-5x\left(x-8\right)\)

\(=\frac{-7}{2}\left(\frac{1}{2}-5\right)+\frac{\left(\frac{1}{4}-\frac{1}{2}-2\right)}{2}+\frac{1}{4}\left(\frac{1}{2}-3\right)-\frac{5}{2}\left(\frac{1}{2}-8\right)\)

\(=\frac{7}{2}.\frac{9}{2}-\frac{9}{8}-\frac{1}{4}.\frac{5}{2}+\frac{5}{2}.\frac{15}{2}\)

\(=\frac{63}{4}-\frac{9}{8}-\frac{5}{8}+\frac{75}{4}=\frac{138}{4}-\frac{7}{4}=\frac{131}{4}\)

Bài 1:

\(D=-3x^2+x+15x-5-3\left(2x^2-5x+2\right)\)

\(=-3x^2+16x-5-6x^2+15x-6\)

\(=-9x^2+31x-11\)

\(=-9\cdot\dfrac{1}{9}+\dfrac{31}{3}-11\)

=-11-1+31/3=-12+31/3=-5/3

b: \(E=x^2+x-56-x^2+7x-10=8x-66\)

\(=-\dfrac{8}{5}-66=-\dfrac{338}{5}\)

c: \(F=-3\left(2x^2+x-16x-8\right)-\left(-3x^2+2x-15x+10\right)-4x^2+24x\)

\(=-6x^2+45x+24+3x^2+13x-10-4x^2+24x\)

\(=-4x^2+82x+14\)

\(=-4\cdot9-82\cdot3+14=-268\)

10 tháng 7 2016

a)

ta có: 1/3x+y+1=0

=> 1/3x+y=-1

ta có : x^3+9x^2y+27xy^2+27y^3

=(x+3y)^3

= [1/3(1/3x+y)]^3

=1/27 . (-1)^3

=1/27 . (-1)

=-1/27

10 tháng 7 2016

\(b\frac{3^{x+y^2}}{3^{x-y^2}}=\frac{3^{x^2+2xy+y^2}}{3^{x^2-2xy+y^2}}=\frac{3^{x^2+y^2}.3^{2xy}}{3^{x^2+y^2}:3^{2xy}}=3^{2xy}.3^{2xy}=3^{\frac{4.1}{2}}=3^2=9\)

5 tháng 10 2021

\(M=3\left(3x+1\right)\left(9x^2-3x+1\right)-\left(x^3+1\right)\)

\(=3\left(27x^3+1\right)-x^3-1=80x^3+2=80.\left(\dfrac{1}{2}\right)^3+2=12\)

5 tháng 10 2021

Sửa đề: \(N=\left(3x+1\right)\left(9x^2-3x+1\right)-\left(x+1\right)\left(x^2-x+1\right)\)

\(N=27x^3+1-x^3-1=26x^3=26.10^3=26000\)

8 tháng 12 2021

ĐK: \(3x\ne\pm y;x\ne0\)

A = \(\dfrac{3x}{3x+y}-\dfrac{x}{3x-y}+\dfrac{2x}{\left(3x-y\right)\left(3x+y\right)}\)

\(\dfrac{3x\left(3x-y\right)-x\left(3x+y\right)+2x}{\left(3x-y\right)\left(3x+y\right)}=\dfrac{6x^2-4xy+2x}{\left(3x-y\right)\left(3x+y\right)}=\dfrac{2x\left(3x-2y+1\right)}{\left(3x-y\right)\left(3x+y\right)}\)

Thay x = 1; y=2, ta có:

A = \(\dfrac{2.1\left(3.1-2.2+1\right)}{\left(3.1-2\right)\left(3.1+2\right)}=0\)